Let's explore Neptune - Orme, Helen; Orme, David, 1948 Mar. 1- (Tunbridge Wells, Kent : Ticktock Entertainment, 2007)
Photographs, illustrations, and simple text provide details about Neptune including what it looks like, its orbit, moons, and rings, and missions to explore the surface of the planet.
Where is Neptune? -- Planet facts -- What's the weather like? -- Neptune's Moons -- Triton -- Neptune's rings -- Neptune in history -- What can we see? -- Missions to Neptune -- Future missions.
Includes index.
3-6.
Keywords: Neptune (Planet) -- Juvenile literature; Neptune (Planet) -- Exploration -- Juvenile literature; Neptune (Planet); Neptune (Planet) -- Exploration; Neptune (Planet); Neptune (Planet) -- Exploration